Design and Analysis of the E-Journal Repository for Final Projects and Student Practices in the D3 Computer Engineering: (Case Study: Harapan Bersama of Polytechnik ) - Ida Afriliana; M.Bahar; Abdul Basit (International Journal of Science, Technology & Management, 2020)
Higher education institutions are the main institutions in creating young people who can be ready to enter the world of work and industry, and one of the educational programs that take part in vocational education. Vocational education is higher education that is directed at focusing certain applied skills. Harapan Bersama of Polytechnic is one of the vocational education institutions that provides Human Resources (HR) to become the younger generation as practitioners in industry, companies, or other stoke holders. In the D3 Computer Engineering Study Program, each batch can graduate approximately 300 graduates, where each graduate will produce one scientific work from the final project research conducted. Likewise, with students who do practical work (KP), every student who does KP will produce scientific papers. But all the results of this scientific work, namely the research report of the Final Project and the Job Training Report are still being submitted to the Study Program in one compact disk (CD). This turned out to be a problem for the Study Program because from each batch, around 300 compact disks (CDs) were collected from the results of scientific work from the practical work and 300 compact disks (CDs) from the final project research outputs. Physical data in the form of a compact disk (CD) requires a large space for its placement. Meanwhile, the condition of the D3 Computer Engineering study program room makes it impossible to place the physical form. And along with technological developments, this physical form can be replaced by soft files in the form of e-journals or e-reports. This needs to be done in line with the paradigm shift from conventional libraries to e-libraries. With the existence of SIPESTA or the information system for the completion of this Final Project, the results of writing scientific papers are uploaded and become a digital trace of all scientific papers that have been carried out by all D3 Computer Engineering students. And so if this data is needed it will be easy to find because the database has been well managed.